Rational Design of Multicolor‐Emitting Chiral Carbonized Polymer Dots for Full‐Color and White Circularly Polarized Luminescence - Ru, Yi; Sui, Laizhi; Song, Haoqiang; Liu, Xingjiang; Tang, Zhiyong; Zang, Shuang‐Quan; Yang, Bai; Lu, Siyu (Angewandte Chemie International Edition, 2021)
Light‐emitting chiral carbonized polymer dots (Ch‐CPDs) are attracting great interest because of their extraordinary photonic properties, but modulating their band‐gap emission, especially at long wavelength, and maintaining their chiral structure to achieve multicolor, high‐emission Ch‐CPDs remains challenging. Reported here for the first time is the synthesis of red‐ and multicolor‐emitting Ch‐CPDs using the common precursors L‐/D‐tryptophan and o‐phenylenediamine, and a solvothermal approach at one temperature. The quantum yield of the Ch‐CPDs was between 31 % and 54 %. Supramolecular self‐assembly provided multicolor‐emitting Ch‐CPDs showing novel circularly polarized luminescence, with the highest dissymmetric factor (glum) of 1×10−2. Importantly, circularly polarized white‐emitting CPDs were fabricated for the first time by tuning the mixing ratio of the three colored Ch‐CPDs in a gel. This strategy affords exciting opportunities for designing functional chiroptical materials. The synthesis of red‐ and multicolor‐emitting chiral carbonized polymer dots (Ch‐CPDs) is reported for the first time. The quantum yield of the Ch‐CPDs is between 31 % and 54 %. Furthermore, these Ch‐CPDs were combined with chiral gels through supramolecular self‐assembly, thereby yielding their multicolor and white circularly polarized luminescence.